Flavor diversification of dark chocolate produced through microwave roasting of cocoa beans. (1st April 2022) - Lemarcq, Valérie; Monterde, Viena; Tuenter, Emmy; Walle, Davy Van de; Pieters, Luc; Sioriki, Eleni; Dewettinck, Koen
Abstract: The impact of microwave roasting cocoa beans on the aroma and phytochemical profile of dark chocolates (70% cocoa) was studied. Three chocolates produced from microwave roasted beans (450 W–55 min, 600 W–35 min, 900 W–20 min) were compared with a chocolate produced from convectively roasted beans (130 °C–30 min). Aroma analysis via HS-SPME-GC-MS indicated that microwave roasting of cocoa beans resulted in chocolate with a distinctive aroma profile, compared to the chocolate produced from convectively roasted beans. Increased power input seems the main inducer of elevated levels of aroma compounds. Interestingly, the impact of the four treatments on the phytochemical profile, measured via LC-HRMS, of the chocolates was rather comparable. Microwave roasting of cocoa beans was more prone to oxidation, but still within acceptable limits. The results validate that microwave roasting is a promising alternative technique that can be used effectively for chocolate production. Graphical abstract: Image 1 Highlights: Microwave roasting serves as a decent alternative for convection roasting. Chocolates with distinctive flavor are obtained when microwave roasting cocoa beans. Similar phytochemical profiles are obtained when convection or microwave roasting. Microwave roasting is more prone to oxidation, but within acceptable limits.